2021
DOI: 10.3390/ijtpp6040045
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Swirling Entropy Waves through an Axial Turbine Stator

Abstract: The transport of entropy waves and their impact on the stage aerodynamics are still open questions. This paper shows the results of an experimental campaign that focuses on the swirling entropy waves advection through an axial turbine stator. The research aims at quantifying the aerodynamic impact of the swirling entropy waves on the first nozzle and characterizing their transport. The disturbance is generated by a novel entropy wave generator that ensures a wide set of different injection parameters. The devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, entropy noise is not strictly associated with the aerodynamic and heat transfer problems discussed in the present paper and is not going to be detailed here. For those who are interested in studying this challenging topic, the works by Gaetani and Persico [58], Gaetani et al [59], Pinelli et al [60], Notaristefano and Gaetani [61,62,63], and Pinelli et al [64] are suggested.…”
Section: Hot Spot Migration In the High-pressure Turbine Stagementioning
confidence: 99%
“…However, entropy noise is not strictly associated with the aerodynamic and heat transfer problems discussed in the present paper and is not going to be detailed here. For those who are interested in studying this challenging topic, the works by Gaetani and Persico [58], Gaetani et al [59], Pinelli et al [60], Notaristefano and Gaetani [61,62,63], and Pinelli et al [64] are suggested.…”
Section: Hot Spot Migration In the High-pressure Turbine Stagementioning
confidence: 99%